Effects of copper source (Intellibond C or copper sulfate) on growth performance, carcass characteristics, pen cleanliness, and economics in finishing pigs - Kyle F Coble; Steven S Dritz; J Usry; Michael D Tokach; Joel M DeRouchey; Robert D Goodband; Jim L Nelssen (Kansas Agricultural Experiment Station Research Reports, 2013)
A total of 1,143 pigs (PIC 337 × 1050, initially 55.3 lb) were used to determine the effects of tribasic copper chloride (TBCC; Intellibond C; Micronutrients Inc., Indianapolis, IN) or copper sulfate (CuSO4) on growth performance, carcass characteristics, pen cleanliness, and economics in a 111-d study. Pens of pigs were randomly allotted to 1 of 6 dietary treatments and balanced based on average pen weight in a completely randomized design with 25 to 28 pigs per pen and 8 pens per treatment. Treatment diets included a corn-soybean meal positive control, a high by-product diet with 30% dried distillers grains with solubles (DDGS) and 15% bakery meal (negative control), or the negative control diet with 75 or 150 ppm copper from CuSO4 or TBCC. All diets were formulated on a standardized ileal digestible (SID) amino acid basis and were 0.05% below the pig's estimated lysine requirement throughout the trial. Pigs fed the corn-soybean meal positive control diet had improved (P<0.01) F/G and tended to have increased ADFI (P<0.08) compared with those fed the negative control, high by-product diet. Pigs fed increasing copper had improved (linear, P<0.01) ADG and ADFI but tended to have slightly poorer (quadratic, P<0.06) F/G. Although no interactions were observed between copper source and level, pigs fed increasing CuSO4 had increased (linear, P<0.02) ADFI, whereas pigs fed increasing TBCC had increased ADG, ADFI, and final BW (linear, P<0.01). Increasing added copper improved (linear, P<0.02) HCW and loin depth, with the greatest response in HCW for pigs fed TBCC (linear, P<0.01). For pen characteristics, pigs fed the high by-product diet had greater (P<0.01) manure buildup and longer wash time than those fed the corn-soybean meal control diet. Addition of copper to diets did not influence pen wash time and had no impact on manure buildup. Economics were calculated on both a constant days on feed and constant market weight basis. Pigs fed either source of copper to a constant days on feed had an increase in feed cost per pig (linear, P<0.01) as well as a higher (P<0.10) revenue per pig. When economics were calculated on feeding pigs to a constant BW, facility costs decreased (linear, P<0.05) with feeding copper. Although no significant differences were detected in income over feed and facility cost for added copper, the greatest numerical advantage to individual copper sources occurred at 75 PPM for CuSO4 ($0.26) and at 150 ppm for TBCC ($1.35 per pig). In summary, feeding increased levels of copper sulfate or TBCC in diets formulated slightly below the estimated SID lysine requirement increased growth rate and feed intake, resulting in increased final BW and HCW. Pigs fed TBCC at 150 ppm had the highest final BW (+12.8 lb) and HCW (+7.7 lb). In addition, the use of added copper in the diets did not increase time required to wash pens. More research is needed to determine whether the amino acid concentration influences the response to copper source and level in diets for growing and finishing pigs.; Swine Day, Manhattan, KS, November 21, 2013
Keywords: Swine day; 2013; Kansas Agricultural Experiment Station contribution; no. 14-044-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1092; Finishing pig; Copper sulfate; Tribasic copper; Chloride; Wash time